IMPLEMENTASI SISTEM PEMUNGUTAN PAJAK KENDARAAN BERMOTOR (PKB) MELALUI LAYANAN DRIVE THRU PADA UPPD SAMSAT BANJARMASIN 2 - Wina Septiana; H. Kasyful Anwar (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
This study aims to determine the implementation of the Motor Vehicle Tax Collection System (PKB) through Drive Thru Services. Based on the results of research that has been carried out by researchers at UPPD Samsat Banjarmasin 2, PKB payment services through the Samsat Drive Thru service are an effort to improve services to provide convenience for the community. These conveniences include simpler requirements and procedures that are more practical and faster than paying PKB at the Samsat Office. The Samsat Drive Thru service has an effect on increasing revenue by 131.83% and contributing to PKB revenue by 1.73% in 2019 and increasing significantly by 4.31% in 2020.